2003
DOI: 10.1088/0029-5515/43/8/304
|View full text |Cite
|
Sign up to set email alerts
|

Development of high performance negative ion sources and accelerators for MeV class neutral beam injectors

Abstract: Operation of accelerator at low pressure is an essential requirement to reduce stripping loss of the negative ions, which in turn results in high efficiency of the NB systems. For this purpose, a vacuum insulated beam source (VIBS) has been developed at JAERI, which reduces the gas pressure in the accelerator by enhanced gas conductance through the accelerator. The VIBS achieves the high voltage insulation of 1 MV by immersing the whole structure of accelerator in vacuum with long (~ 1.8 m) insulation distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Large negative ion sources are in operation at JT60-U [5,6] and LHD [7,8], representing roughly a 2/3 and 1/3 ITER size, respectively. These sources are filament driven arc sources, based on the so-called KAMABOKO type [9].…”
Section: Introductionmentioning
confidence: 99%
“…Large negative ion sources are in operation at JT60-U [5,6] and LHD [7,8], representing roughly a 2/3 and 1/3 ITER size, respectively. These sources are filament driven arc sources, based on the so-called KAMABOKO type [9].…”
Section: Introductionmentioning
confidence: 99%
“…The H 2 gas is considered to prevent the creeping discharge along the FRP insulator surface. It was found that the VIBS could sustain 1 MV under the presence of H 2 in the range of 0.07 -0.2 Pa [9,10]. This pressure range corresponds to that of the accelerator during the operation, and it was confirmed that the VIBS can sustain 1 MV stably for more than 2 hours under the H 2 gas feed of this range.…”
Section: Improvement Of 1 MV Holding Capability By Large Stress Ringmentioning
confidence: 92%
“…The beam heat loads on the accelerator grids and injection port limit the pulse length of the injection. The stripped electrons [60] are the main cause of the former heat load. Reduction of gas load in the accelerator and distribution of the electron load on the grids will be investigated.…”
Section: Nbimentioning
confidence: 99%